Evaluation of nutritional value of prickly chaff flower (Achyranthes aspera) as fish feed ingredient - KUMAR, NEELESH; SHARMA, JAIGOPAL; KUMAR, GUDDU; SHRIVASTAV, AVANISH KUMAR; TIWARI, NEHA; BEGUM, AJIMA; CHAKRABARTI, RINA (The Indian Journal of Animal Sciences, 2021)
The nutritional value of seeds and leaves of Achyranthes aspera as fish feed ingredients was evaluated. The protein and lipid contents were higher in seeds and ash content was higher in leaves. In seeds, total 18 essential and non-essential amino acids were present; total 17 amino acids were found in leaves, cysteine was absent. The essential and non-essential amino acid contents were higher in seeds compared to leaves except, leucine, tryptophan, valine, alanine and tyrosine. Taurine content was higher in leaves. Higher saturated, monounsaturated and n-6 polyunsaturated fatty acids (n-6 PUFA) contents were observed in seeds, whereas, n-3 PUFA level was higher in leaves. In seeds, oleic and linoleic acid levels were 1863.34±9.25 and 3342.05±8.05 mg/100 g, respectively; α- linolenic acids level in leaves was 1058.07±3.71 mg/100 g. Vitamins A, D2, E, B1, B2, B6, B12 and C were present in seeds; vitamins A, D2, E, B2 and B12 were found in leaves. In seeds and leaves, four macro, nine trace and four ultra-trace minerals were found and contents were higher in leaves, except zinc. In seeds and leaves, iron contents were 76.82±4.15 and 293.73±11.40 μg/g, respectively. Thus, seeds and leaves are rich sources of nutrients.